2017
DOI: 10.5937/zrffp47-14984
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits as predictors of depression, anxiety, and stress with secondary school students of final years

Abstract: The main aim of this research is to examine the predictive power of personality traits, as defined by the Big five model of personality in expressing depression, anxiety, and stress with secondary school students of final years. The research was conducted on a sample of 977 secondary school students in the third and fourth grade from ten secondary schools in Niš. The gender structure of the sample was as follows: 397 boys and 607 girls. The following instruments were used in the research: Depression Anxiety St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 9 publications
2
4
0
1
Order By: Relevance
“…Neuroticism positively correlated with stress, anxiety and depression. These results were also found by Vujičić and Ranđelović (2017) and Mostafaei et al (2019), and similar results were reported by other studies (Brailovskaia & Margraf, 2016;Ervasti et al, 2019;Gramstad et al, 2013;Milić et al, 2019;Mousavi & Essazadegan, 2016;Pereira-Morales et al, 2019;Seto et al, 2019;Sørengaard et al, 2019). In contrast, (A) negatively correlated with stress, anxiety and depression.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Neuroticism positively correlated with stress, anxiety and depression. These results were also found by Vujičić and Ranđelović (2017) and Mostafaei et al (2019), and similar results were reported by other studies (Brailovskaia & Margraf, 2016;Ervasti et al, 2019;Gramstad et al, 2013;Milić et al, 2019;Mousavi & Essazadegan, 2016;Pereira-Morales et al, 2019;Seto et al, 2019;Sørengaard et al, 2019). In contrast, (A) negatively correlated with stress, anxiety and depression.…”
Section: Resultssupporting
confidence: 90%
“…Mousavi and Essazadegan (2016) found that anxiety negatively correlated with conscientiousness and depression negatively correlated with extraversion. However, in the study by Vujičić and Ranđelović (2017) extraversion negatively influenced anxiety, and conscientiousness negatively predicts anxiety and depression. Morevover, the correlation between consciousness and depression was found previously by different studies (Seto et al, 2019;Vujičić & Ranđelović, 2017).…”
Section: Resultsmentioning
confidence: 60%
See 3 more Smart Citations